Assessing Fire Safety Compliance and it's Impact on Occupational Health Outcomes Among Palm Oil Workers in Ika Lga, Delta State - Henry Ikechukwu Imah; Sunday Nathaniel Nwabuwe (dialektika kontemporer, 2026)
Fire safety compliance remains a critical determinant of occupational health and safety, particularly in high-risk industries such as palm oil processing. This study assessed fire safety compliance and its impact on occupational health outcomes among palm oil workers in Ika Local Government Area, Delta State, Nigeria. The study was guided by three objectives focusing on the level of fire safety compliance, the prevalence of occupational health hazards, and the relationship between compliance practices and workers’ health outcomes. A descriptive survey research design was adopted. The population consisted of palm oil workers in selected mills within the study area, while a stratified sampling technique was used to select respondents. Data were collected using a structured questionnaire validated by experts and tested for reliability using Cronbach’s alpha. Descriptive statistics (mean and standard deviation) and inferential statistics (Pearson correlation) were used for data analysis. Findings revealed that the level of fire safety compliance among palm oil workers was moderately low, with inadequate provision and use of fire extinguishers, poor emergency preparedness, and limited safety training. The study also showed a high prevalence of occupational hazards such as burns, respiratory issues, and minor fire-related injuries. Furthermore, a significant positive relationship was found between fire safety compliance and improved occupational health outcomes. The study concludes that strengthening fire safety measures can significantly reduce occupational health risks among palm oil workers. It recommends regular safety training, enforcement of safety regulations, and provision of adequate fire safety equipment in palm oil processing facilities.